Advancements in prognostic factors and survival outcomes following pulmonary metastasectomy for head and neck cancers - Grapatsas, Konstantinos; Ehle, Benjamin; Dahm, Manfred; Papatriantafyllou, Athanasios; Koletsis, Efstratios; Mulita, Francesk; Liolis, Elias; Tasios, Konstantinos; Panagiotopoulos, Ioannis; Katinioti, Anastasia; Katsakiori, Paraskevi; Litsas, Dimitrios; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2024)
Surgical treatment of lung metastases originating from head and neck tumors has shown favorable outcomes with low incidence of complications and mortality. This study aims to investigate survival and prognostic factors following pulmonary metastasectomy for head and neck cancers. A comprehensive review of the literature was conducted through the Medline database, focusing on English-language studies related to surgical treatment of lung metastases from head and neck cancers. Lung metastases occur frequently in patients with head and neck tumors, significantly impacting overall survival. Multidisciplinary assessment is crucial in determining treatment strategies, with notable improvements in survival rates observed over recent decades. Various studies have reported survival outcomes and prognostic factors, highlighting the significance of factors such as primary tumor localization, histology, and completeness of resection. Pulmonary metastasectomy with curative intent for head and neck cancers is a safe and effective treatment option that can prolong survival in selected patients.